Different Response of Ptch Mutant and Ptch Wildtype Rhabdomyosarcoma Toward SMO and PI3K Inhibitors - Geyer, Natalie; Ridzewski, Rosalie; Bauer, Julia; Kuzyakova, Maria; Dittmann, Kai; Dullin, Christian; Rosenberger, Albert; Schildhaus, Hans-Ulrich; Uhmann, Anja; Fulda, Simone; Hahn, Heidi (Frontiers in Oncology, 2018)
Rhabdomyosarcoma (RMS) is the most common pediatric soft tissue sarcoma with poor prognosis. RMS frequently show activity of PI3K signaling. In addition, they show Hedgehog (HH) pathway activity, which is predominantly seen in the embryonal subtype (ERMS). Our in vitro and in vivo data demonstrate that Smoothened (SMO) antagonists strongly inhibit HH signaling and efficiently reduce proliferation and growth of ERMS showing canonical HH signaling activity due to germline mutations in Ptch. Beyond that the tumors are also highly responsive towards PI3K inhibition, which does not involve modulation of HH signaling activity. Furthermore specific combinations of SMO antagonists and PI3K inhibitors can enhance anticancer effects of either single drug. This is different in sporadic ERMS, in which mutations in components of the HH pathway are rare. Thus, cell lines derived from sporadic ERMS are nonresponsive to stimulation by SHH or SAG. Moreover, SMO antagonists are not efficient and apparently exert off-target effects. In contrast, PI3K/AKT/mTOR inhibitors efficiently downregulate HH signaling activity in these cells and potently inhibit cellular proliferation. This indicates that HH signaling is non-canonically activated via the PI3K pathway in sporadic ERMS. Furthermore, these data suggest that a medication of sporadic ERMS with SMO inhibitors either requires pretesting or a screen for PTCH mutations and that PI3K inhibitors are in general a better and more reliable therapeutic option for these tumors.